2002
DOI: 10.1038/ncb754
|View full text |Cite
|
Sign up to set email alerts
|

Polycystin-2 is an intracellular calcium release channel

Abstract: Polycystin-2, the product of the gene mutated in type 2 autosomal dominant polycystic kidney disease (ADPKD), is the prototypical member of a subfamily of the transient receptor potential (TRP) channel superfamily, which is expressed abundantly in the endoplasmic reticulum (ER) membrane. Here, we show by single channel studies that polycystin-2 behaves as a calcium-activated, high conductance ER channel that is permeable to divalent cations. Epithelial cells overexpressing polycystin-2 show markedly augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
683
5
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 635 publications
(743 citation statements)
references
References 39 publications
48
683
5
2
Order By: Relevance
“…Nevertheless, it is possible that plasma membrane expression of PKD2 is not sufficient for function, but perhaps interactions with other subunits are needed for channel activity. It was subsequently shown that PKD2 functioned as a novel intracellular Ca 2+ channel which was activated in response to increases in intracellular Ca 2+ concentration [45]. Single channel studies indicated that ER-reconstituted PKD2 displayed channel activity and Ca 2+ imaging experiments revealed that PKD2 overexpression enhanced the amplitude and duration of G protein coupled receptor (GPCR) -induced Ca 2+ release transients in the kidney epithelial cell line, LLC-PK1 [45].…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, it is possible that plasma membrane expression of PKD2 is not sufficient for function, but perhaps interactions with other subunits are needed for channel activity. It was subsequently shown that PKD2 functioned as a novel intracellular Ca 2+ channel which was activated in response to increases in intracellular Ca 2+ concentration [45]. Single channel studies indicated that ER-reconstituted PKD2 displayed channel activity and Ca 2+ imaging experiments revealed that PKD2 overexpression enhanced the amplitude and duration of G protein coupled receptor (GPCR) -induced Ca 2+ release transients in the kidney epithelial cell line, LLC-PK1 [45].…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
“…It was subsequently shown that PKD2 functioned as a novel intracellular Ca 2+ channel which was activated in response to increases in intracellular Ca 2+ concentration [45]. Single channel studies indicated that ER-reconstituted PKD2 displayed channel activity and Ca 2+ imaging experiments revealed that PKD2 overexpression enhanced the amplitude and duration of G protein coupled receptor (GPCR) -induced Ca 2+ release transients in the kidney epithelial cell line, LLC-PK1 [45]. It was shown in the same study that PKD2 overexpression did not alter the Ca 2+ content of the intracellular stores as the response to the SERCA inhibitor, thapsigargin was identical between mock-and PKD2-transfected cells.…”
Section: Functional Compartmentalization Of Pkd2mentioning
confidence: 99%
See 2 more Smart Citations
“…These include the basolateral plasma membrane of epithelial cells [64]; the endoplasmic reticulum This is the Pre-Published Version (ER) where it may operate as a Ca 2+ -release channel [65], and the primary cilia where it is thought to participate in mechanosensation [66]. The function of TRPP2 in primary cilia has been linked to the formation of kidney cysts in vertebrates.…”
Section: Trp Channels Are Involved In the Generation Of The Ca 2+ Sigmentioning
confidence: 99%